(untitled) (Eurasian Research Bulletin, 2022)
Blended learning is an educational technology that combines and interpenetrates face-toface and e-learning with the ability for the student to independently choose the time, place, pace and trajectory of learning. Thus, blended learning technology can be considered as a synergistic technology that allows you to more effectively use the advantages of both face-to-face and e-learning, and neutralize or mutually compensate for the shortcomings of each of them.